Segmental Femoral Ostectomy for the Reconstruction of Femoropatellar Joint in Dogs with Grade IV Medial Patellar Luxation - Nagahiro, Yukari; Murakami, Sawako; Kamijo, Keiji; Shimada, Masakazu; Kanno, Nobuo; Suzuki, Shuji; Harada, Yasuji; Hara, Yasushi (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objective The aim of this study was to describe a new surgical method of segmental femoral ostectomy for the reconstruction of the femoropatellar joint (FPJ) in dogs with medial patellar luxation (MPL) grade IV.Study Design The medical records of six dogs that underwent segmental femoral ostectomy to reconstruct the FPJ for MPL grade IV were retrospectively reviewed. The data included breed, age, body weight, comorbidities, history of orthopaedic abnormalities, pre- and postoperative radiographic findings, morphological indicators measured on three-dimensional computed tomographic multiplanar reconstruction images, surgical methods and postoperative complications.Outcomes Eleven hindlimbs with MPL grade IV in six dogs underwent segmental femoral ostectomy to reconstruct the FPJ with the four basic surgical procedures. Six stifle joints with femoral varus deformity were treated by closing wedge ostectomy and segmental ostectomy, while five stifle joints were treated by segmental ostectomy alone. The mean resected femoral length was 11.7 mm. The mean resected femoral length relative to the preoperative femoral length was 14.3%. The stability and congruity of the FPJ was markedly improved, with an increased range of motion in all dogs compared with their preoperative status.Conclusion Segmental femoral ostectomy was a useful treatment method for MPL grade IV with shortened quadriceps muscle length relative to the femoral length. Reconstruction of the FPJ is important for recovery of limb function.
Keywords: medial patellar luxation; segmental femoral ostectomy; toy-breed dog; patella alta; femoral varus deformity